Stable molecular transformation of Toxoplasma gondii: a selectable dihydrofolate reductase-thymidylate synthase marker based on drug-resistance mutations in malaria. - Donald, R G (1993)
To facilitate genetic analysis of the protozoan parasite Toxoplasma gondii, sequences derived from the parasite's fused dihydrofolate reductase-thymidylate synthase (DHFR-TS) gene have been used to produce vectors suitable for stable molecular transformation. Mutations introduced into the DHFR coding region by analogy with pyrimethamine-resistant malaria confer drug resistance to Toxoplasma, providing useful information on the structure of fused DHFR-TS enzymes and a powerful selectable marker for molecular genetic studies. Depending on the particular drug-resistance allele employed and the conditions of selection, stable resistance can be generated either by single copy nonhomologous insertion into chromosomal DNA or by massively amplified transgenes. Frequencies of integration are independent of selection, and transgenes are stable without continued selection. Cointegration of a reporter gene adjacent to the selectable marker (under the control of an independent promoter) shows no loss of the cointegrated sequences over many parasite generations. By bringing the full power of molecular genetic analysis to bear on Toxoplasma, these studies should greatly facilitate the development of a model genetic system for Apicomplexan parasites.